Effect of Asset Inventory, Legal Asset Audit and Control Monitoring on Asset Optimization - Firmansyah, Djamal; Cris Kuntadi (Dinasti Publisher, 2023)
This Literature Review aims for this article to map the effect of asset inventory, legal audit and control oversight on asset optimization. As independent variables, namely asset inventory, legal audit and control oversight while the dependent variable is asset optimization in a study of state financial management literature. The purpose of writing this article is as a literature review in order to build hypotheses about the influence between variables for use in further research. Based on the results of this literature review article, it is known that asset inventory has an effect on asset optimization, legal audits have an effect on asset optimization, control oversight has an effect on asset optimization.